AB1031 Profile of a series of 196 patients treated with IV zoledronic acid. (23rd January 2014) - Gonzalez Cabanas, M.; Cerdà, D.; Roig, D.; Reina, D.; Fíguls, R.; García Diaz, S.; Juanola, X.; Nolla, J.M.; Corominas, H.
Abstract : Background: Zoledronic acid is a third generation intravenous (IV) drug, indicated for the treatment of Osteoporosis, among other diseases, including Paget's disease and Reflex sympathetic dystrophy. Objectives: To describe the clinical features of a series of 196 patients treated with zoledronic acid ev in the period 2008-2011 in two hospitals in Barcelona. To analyze the indications, clinical and densitometric characteristics and treatment side effects of zoledronic acid. Methods: A total of 196 patients received zoledronic acid. We performed a retrospective design reviewing medical records of these patients. We collected epidemiological, clinical, densitometric parameters and side effects to treatment. Results: Of the 196 patients who received zoledronic acid, 157 were women (80.1%) and 39 men (19.9%). 94% of patients (184) had Osteoporosis, 4% (8) Paget, 1 patient had SAPHO, 1 Reflex sympathetic dystrophy, 1 neuropathic arthropathy and 1 osteogenesis imperfecta Of the total of Osteoporosis treated, 84% had primary osteoporosis and 16% had secondary osteoporosis. 47% of patients had received prior treatments for Osteoporosis (66.5% bisphosphonates, 16.2% estrontium ranelate, 4.8% raloxifene, 8% PTH and 4.5% calcitonin). 51% of patients had previous fractures (62.5% vertebral fractures, 18.7% Colles' fracture, 12.5% fracture of the femur and 6.3% in other locations). Only 4.7% presented a new fracture after starting treatment. Average patients' densitometric values before starting the treatment were: T-score -3.3 at the lumbar spine and -2.3 at femoral neck. Only 9.5% of patients experienced adverse effects, 75% of them flu like syndrome. Among the other side effects, there was a case of hypocalcemia and another one of keratoconjunctivitis sicca. Conclusions: Zoledronic acid is indicated primarily as intravenous treatment for Osteoporosis, in cases of intolerance to oral treatment and refractory Osteoporosis to previous treatments. Most cases have a history of fracture. This is an effective and safe treatment with a low rate of adverse effects. Disclosure of Interest: None Declared